2021
DOI: 10.3390/s21196535
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Optical Sensing Based on Phase Shift of Waves Supported by a One-Dimensional Photonic Crystal

Abstract: Interferometric methods of optical sensing based on the phase shift of the Bloch surface waves (BSWs) and guided waves (GWs) supported by a one-dimensional photonic crystal are presented. The photonic crystal, composed of six SiO2/TiO2 bilayers with a termination layer of TiO2, is employed in the Kretschmann configuration. Under resonance condition, an abrupt phase change is revealed, and the corresponding phase shift is measured by interferometric techniques applied in both the spectral and spatial domains. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…1DPhC was fabricated (Meopta, Přerov, Czech Republic) by a sputtering thin film deposition technique, and exact parameters such as layer thicknesses and dispersions were provided by techniques of scanning electron microscopy (SEM) and spectral ellipsometry. An SEM image (see Figure 1 a) captured by a scanning electron microscope (Quanta 650 FEG, FEI Company, Hillsboro, OR, USA) confirmed that the 1DPhC is composed of a system of six bilayers of TiO /SiO and a termination layer of TiO demanded for BSW-based sensing applications, as presented in a previous paper [ 52 ]. The SEM image obtained for a different magnification can also be found in the same paper.…”
Section: Materials Characterizationsupporting
confidence: 69%
See 2 more Smart Citations
“…1DPhC was fabricated (Meopta, Přerov, Czech Republic) by a sputtering thin film deposition technique, and exact parameters such as layer thicknesses and dispersions were provided by techniques of scanning electron microscopy (SEM) and spectral ellipsometry. An SEM image (see Figure 1 a) captured by a scanning electron microscope (Quanta 650 FEG, FEI Company, Hillsboro, OR, USA) confirmed that the 1DPhC is composed of a system of six bilayers of TiO /SiO and a termination layer of TiO demanded for BSW-based sensing applications, as presented in a previous paper [ 52 ]. The SEM image obtained for a different magnification can also be found in the same paper.…”
Section: Materials Characterizationsupporting
confidence: 69%
“…In both cases, the resonance wavelength shift versus the RH can be well fitted by linear functions so that the sensitivity to RH, defined similarly to Equation ( 6 ) as the change of the position of the dip with respect to the change in the relative humidity , reaches 0.156 nm/%RH and 0.136 nm/%RH, respectively. Thus, sensing based on the cavity-mode resonances outperforms available techniques [ 35 , 52 ] utilizing surface plasmon and Bloch waves resonances, whispering gallery, and guided mode resonances as well. Using a similar relation to Equation ( 7 ), the FOM of the RH measurement reaches 0.047 %RH and 0.036 %RH , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…, 10) have thicknesses t j , as schematically shown in Figure 2; their values are specified in Table 1. The refractive index dispersion of a glass substrate and the layers of SiO 2 and TiO 2 was obtained from the ellipsometric data for a 1DPhC including the same layer materials [61]. In the case of the glass substrate, the refractive index (RI) as a function of wavelength is expressed by the Cauchy formula:…”
Section: Materials Characterizationmentioning
confidence: 99%
“…Optical applications based on 1DPhCs with cavity-mode resonances represent an effective alternative to standard ones. They can be used as planar waveguides, and the guided waves can be used in sensing applications [3]. Moreover, the Bloch surface waves (BSWs) propagating along the interface of the 1DPhC and external medium are widely used in sensing area [4,5].…”
Section: Introductionmentioning
confidence: 99%